A tale of two tails: exploring stellar populations in the tidal tails of NGC 3256. Issue 1 (30th May 2016) - Rodruck, Michael; Konstantopoulos, Iraklis; Knierman, Karen; Fedotov, Konstantin; Mullan, Brendan; Gallagher, Sarah; Durrell, Patrick; Ciardullo, Robin; Gronwall, Caryl; Charlton, Jane
Abstract: We have developed an observing programme using deep, multiband imaging to probe the chaotic regions of tidal tails in search of an underlying stellar population, using NGC 3256's 400 Myr twin tidal tails as a case study. These tails have different colours of u − g = 1.05 ± 0.07 and r − i = 0.13 ± 0.07 for NGC 3256W, and u − g = 1.26 ± 0.07 and r − i = 0.26 ± 0.07 for NGC 3256E, indicating different stellar populations. These colours correspond to simple stellar population ages of $288^{+11}_{-54}$ and $841^{+125}_{-157}$  Myr for NGC 3256W and NGC 3256E, respectively, suggesting that NGC 3256W's diffuse light is dominated by stars formed after the interaction, while light in NGC 3256E is primarily from stars that originated in the host galaxy. Using a mixed stellar population model, we break our diffuse light into two populations: one at 10 Gyr, representing stars pulled from the host galaxies, and a younger component, whose age is determined by fitting the model to the data. We find similar ages for the young populations of both tails ($195^{-13}_{+0}$ and $170^{-70}_{+44}$  Myr for NGC 3256W and NGC 3256E, respectively), but a larger percentage of mass in the 10 Gyr population for NGC 3256E ($98^{+1}_{-3}\hbox{ per cent}$ versus $90^{+5}_{-6}\hbox{ per cent}$ ). Additionally, we detect 31 star cluster candidates in NGC 3256W and 19 in NGC 2356E, with median ages of 141 and 91 Myr, respectively. NGC 3256E contains several young (<10 Myr), low-mass objects with strong nebular emission, indicating a small, recent burst of star formation.